The Effectiveness of a Business Statistics-Based Market Validation Capstone Project in Improving Entrepreneurial Readiness among Generation Z - Annisa Ramadhan; Hussein Gibreel Musa (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
Generation Z students have strong potential to develop new business ventures due to their familiarity with digital technology, social media, and rapidly changing consumer trends. However, business ideas developed in entrepreneurship courses are often based on group assumptions rather than empirical market evidence. This investigation seeks to assess the influence of a Business Statistics based Market Validation Capstone Project on the entrepreneurial readiness found among Generation Z students. To carry out the study, the researchers used a quantitative framework and a one group pretest posttest design. The subjects consisted of Digital Business undergraduates concurrently enrolled in Business Statistics and Entrepreneurship courses. The intervention consisted of a Market Validation Capstone Project, including questionnaire development, data collection from target consumers, market validation analysis, and the use of findings as the basis for business decision-making. Entrepreneurial readiness was measured using a Likert-scale questionnaire before and after the intervention. Data were analyzed using descriptive statistics, validity and reliability tests, normality testing, and paired sample t-test. The results showed a significant increase in students’ entrepreneurial readiness after completing the Market Validation Capstone Project. This finding indicates that integrating Business Statistics into entrepreneurship learning through market validation activities effectively strengthens students’ readiness to develop, evaluate, and offer new business products. The study concludes that data-driven capstone learning can support entrepreneurial education by encouraging students to make business decisions based on empirical evidence rather than assumptions.